Diesel engine catalyst based on high-entropy oxide ultrafine particles and preparation method

By using CeFeMnCoNiOx five-membered high-entropy composite metal oxide nanoparticles and PtO2 in diesel engine oxidation catalysts, combined with CeO2, ZrO2 and γ-Al2O3, the problems of high cost and poor performance of precious metal materials are solved, and efficient PM, HC and CO purification reduces production and maintenance costs.

CN119186591APending Publication Date: 2024-12-27HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411330024.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The high cost of precious metal materials in existing diesel engine oxidation catalysts is the high resistance to sulfur poisoning, thermal aging and coking resistance, which leads to an increase in production and maintenance costs, and the limited number of catalytic active sites, making it difficult to meet the requirements of efficient emission regulations.

Method used

CeFeMnCoNiOx five-membered high-entropy composite metal oxide nanoparticles and a small amount of PtO2 as the main catalytic active components, combined with CeO2, ZrO2 and γ-Al2O3, catalytic coatings were prepared by ultrasonic oscillation and carbon black template materials, which significantly improved the catalytic activity of the catalyst and Durability.

Benefits of technology

It significantly reduces the load of precious metal materials, improves the anti-sulfur poisoning, thermal aging and coking properties of the catalyst, increases the number of catalytic active sites, improves the purification efficiency of PM, HC and CO, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186591A_ABST
    Figure CN119186591A_ABST
Patent Text Reader

Abstract

The invention discloses a diesel engine catalyst based on high-entropy oxide ultrafine particles and a preparation method of the diesel engine catalyst. CeFeMnCoN iOx five-element high-entropy composite metal oxide nanoparticles and PtO2 are used as main catalytic active components of the catalyst, and CeO2, ZrO2, gamma-Al2O3 and cordierite honeycomb ceramics are used as auxiliary components of the catalyst. The catalyst is packaged in DOC, and pollutants such as PM, HC and CO discharged by a diesel engine can be efficiently purified. The main catalytic active component of the quinary high-entropy composite metal oxide nanoparticles has the advantages of sulfur resistance, heat resistance and low cost, and the catalytic activity of the catalyst is improved and a high-activity temperature window is expanded through the synergistic interaction effect of the multielement high-entropy metal oxide and PtO2. According to the preparation method, the dispersion effect of the precursor of the multi-element high-entropy metal oxide is remarkably improved, the number of catalytic activity points of the multi-element high-entropy metal oxide is increased, the overall catalytic activity of the catalyst is enhanced, and precious metal is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of purification of exhaust pollutants from vehicle internal combustion engines, and in particular relates to a diesel engine catalyst based on ultrafine high entropy oxide particles and a preparation method thereof. Background Art

[0002] Diesel engines are powerful, highly efficient, and durable. They are the dominant power source for large and medium-sized passenger and freight transport vehicles at home and abroad. However, due to the limitation of combustion mode, compared with other fuel type engines, diesel engines have higher PM emissions. Their wide application in economic and social life has caused serious harm to air quality and human health. Since diesel engine in-cylinder combustion optimization technology has limited control potential for in-cylinder PM formation and emission, post-treatment purification technology for diesel engine exhaust PM pollutants has become a research hotspot in the industry. In addition to the diesel particulate filter (DPF) based on the principle of physical interception, the diesel oxidation catalyst (DOC) based on the principle of PM catalytic oxidation is also regarded as an efficient purification method for diesel engine exhaust PM. At present, the efficient synergy of DOC and DPF is the most commonly used solution to meet the national VI emission regulations for diesel engine PM emissions. In addition, while purifying PM, DOC can also catalytically oxidize HC and CO in diesel engine exhaust to achieve the joint removal of multiple pollutants.

[0003] The oxidation catalyst currently used in diesel engine DOC that meets the National VI emission regulations is a loaded catalyst based on a precious metal main catalytic active component / transition metal oxide co-catalyst / γ-Al2O3 coating / honeycomb ceramic carrier structure. The catalyst of this structure has a high catalytic activity for PM oxidation reaction. However, the high cost of precious metal raw materials has pushed up the production cost of the after-treatment system and the diesel engine, and worsened the competitiveness of diesel engines in the field of medium and heavy-duty transport vehicle power sources compared with natural gas engines, pure electric power systems and other types of power units; at the same time, the precious metal components have poor resistance to sulfur poisoning, thermal aging, and coking. In order to extend the service life of precious metal-based catalysts, manufacturers have formulated extremely stringent usage specifications and maintenance procedures for diesel engines that meet the National VI emission regulations, which has increased the use and maintenance costs of diesel engines.

[0004] In recent years, the application of high entropy oxide (HEO) materials in the field of pollutant purification has gradually attracted the attention of the industry. HEO generally refers to a single-phase solid solution composed of 5 or more metal oxides with the same or similar molar ratio, and the more metal types and the closer the mole fractions of various metal components, the higher the conformational entropy of the single-phase solid solution composite oxide. Due to its unique physical and chemical property optimization mechanisms such as high entropy effect, lattice distortion effect, slow diffusion effect, and cocktail effect, HEO has great potential to become the main catalytic active component of the efficient catalyst for the oxidation reaction of diesel exhaust pollutants. On the other hand, the smaller the particle size of the main catalytic active component in the catalytic coating on the surface of the DOC pores, the larger the specific surface area of ​​the active component, and the greater the number of catalytic active sites, which can also achieve the improvement of the catalytic activity of the catalyst.

[0005] Based on the above technical requirements, the present invention proposes a supported diesel engine oxidation catalyst with CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles and a small amount of PtO2 as the main catalytic active components. Summary of the invention

[0006] The purpose of the present invention is to overcome the above problems existing in the prior art and to provide a diesel engine catalyst based on ultrafine particles of high entropy oxide and a preparation method thereof.

[0007] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0008] A diesel engine catalyst based on ultrafine high entropy oxide particles, characterized in that it comprises:

[0009] CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles, PtO2, CeO2, ZrO2, γ-Al2O3 and 400 mesh cordierite honeycomb ceramics;

[0010] Among them, CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 are mainly catalytic active components, and the mass percentage of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 is 90-98%: 2-10%, and the sum of the mass percentages is 100%.

[0011] Furthermore, in the CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles, the molar percentages of Ce element, Fe element, Mn element, Co element and Ni element are 20-35%: 15-25%: 15-25%: 15-25%: 10-20%, and the sum of the molar percentages is 100%.

[0012] Furthermore, CeO2 and ZrO2 are used as promoters, and the mass percentages of CeO2 and ZrO2 are: 70-90%: 10-30%, and the sum of the mass percentages is 100%.

[0013] Furthermore, γ-Al2O3 is used as a coating additive, and the γ-Al2O3 comes from pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol, the mass percentages of pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol are: 75-90%: 10-25%, and the sum of the mass percentages is 100%.

[0014] Furthermore, the catalytic coating of the diesel engine catalyst is composed of a main catalytic active component, a co-catalyst and a coating additive, and the mass percentages of the main catalytic active component, the co-catalyst and the coating additive are: 2-8%: 3-12%: 80-95%, and the sum of the mass percentages is 100%.

[0015] Furthermore, the diesel engine catalyst is composed of the catalytic coating and 400 mesh cordierite honeycomb ceramics, and the 400 mesh cordierite honeycomb ceramics are the carrier of the diesel engine catalyst, and the catalytic coating needs to be coated on the carrier, and the mass percentage range of the catalytic coating and the carrier is: 15-30%: 85-70%, and the sum of the mass percentages is 100%.

[0016] The present invention also provides a method for preparing a diesel engine catalyst based on ultrafine high entropy oxide particles, comprising the following steps:

[0017] Step 1: Catalyst composition design: prepare the following materials in proportion: CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles, PtO2, CeO2, ZrO2, γ-Al2O3;

[0018] Step 2: Preparation of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles: Weigh the determined masses of Ce(NO3)3·6H2O, Fe(NO3)3·9H2O, Mn(CH3COO)2, Co(NO3)2·6H2O, Ni(NO3)2·6H2O and glucose, and carbon black with a mass ranging from 0.5 to 1 times the sum of the masses of Ce(NO3)3·6H2O, Fe(NO3)3·9H2O, Mn(CH3COO)2, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O and a median particle size not exceeding 500 nm, and mix the The seven raw materials are added together into deionized water weighed according to the ratio of 1g carbon black to 10-20mL deionized water, and ultrasonic oscillation is performed for 2-4h, and then the mixture of the seven raw materials and deionized water is heated while ultrasonic oscillation, so that the mixture is evaporated to dryness after 6-8h to form a wet gel; the wet gel is then dried at 80-110°C for 6-12h to obtain a dry gel; the dry gel is heated to 350°C in a muffle furnace at a rate of 3°C:min and maintained for 2h, and then heated to 600-800°C at a rate of 10°C:min and calcined for 3-6h to obtain CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles;

[0019] Step 3: Preparation of coating slurry: Weigh a certain mass of Pt(NO3)2, Ce(NO3)3·6H2O, Zr(NO3)4·5H2O, pure γ-Al2O3 powder, aluminum sol, polyethylene glycol with a molecular weight of 20,000, and CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles prepared in step 2, add the seven raw materials together into deionized water with a mass equivalent to 5 to 15 times the mass of the planned catalytic coating, and form a slurry by ultrasonic oscillation; adjust the pH value of the slurry to within the range of 4 to 6 with NaOH or HNO3, and grind the slurry on a grinder to D 50 The particle size is in the range of 800 to 1000 nm, and the ground slurry is stirred at 50 to 70° C. for 48 to 72 hours to obtain a coating slurry;

[0020] Step 4: Coating: Design the mass of the carrier to be coated with the catalytic coating; weigh the determined mass of the carrier, immerse the carrier in the coating slurry at 50-70°C, and ensure that the upper end surface of the carrier is slightly higher than the slurry surface; after the slurry is naturally lifted and fills all the pores of the carrier, take the carrier out of the slurry, blow off the residual fluid in the pores, dry at 80-110°C for 4-16 hours, and then calcine at 500-600°C for 2-4 hours; repeat the above-mentioned impregnation, drying and calcination processes 2-3 times to obtain a diesel engine catalyst based on high entropy oxide ultrafine particles.

[0021] Further, in step 2, the mass of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and the molar numbers of Ce, Fe, Mn, Co and Ni elements in CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles are calculated according to step 1; combined with 1 mol Ce prepared from 434.2g Ce(NO3)3·6H2O, 1 mol Fe prepared from 404g Fe(NO3)3·9H2O, 1 mol Mn prepared from 173g Mn(CH3COO)2, 1 mol Co prepared from 291g Co(NO3)2·6H2O, 1 mol Ni prepared from 290.8g Ni(NO3)2·6H2O, and the ratio of the sum of the molar numbers of Ce, Fe, Mn, Co and Ni elements in CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles to the molar number of glucose being 1:1 to 2, and 1 mol Mn prepared from 434.2g Ce(NO3)3·6H2O, 1 mol Fe prepared from 404g Fe(NO3)3·9H2O, 1 mol Mn prepared from 173g Mn(CH3COO)2, 1 mol Co prepared from 291g Co(NO3)2·6H2O, and 1 mol Ni prepared from 290.8g Ni(NO3)2·6H2O. The mass of Ce(NO3)3·6H2O, Fe(NO3)3·9H2O, Mn(CH3COO)2, Co(NO3)2·6H2O, Ni(NO3)2·6H2O and glucose required to prepare the CeFeMnCoNiOx five-component high-entropy composite metal oxide nanoparticles was calculated based on the conversion ratio of glucose weighing 180.2 g.

[0022] Furthermore, in step three, the masses of PtO2, CeO2 and ZrO2 and the mass of γ-Al2O3 coating additive required for preparing the catalytic coating are calculated based on step one; the masses of Pt(NO3)2, Ce(NO3)3·6H2O, Zr(NO3)4·5H2O and aluminum sol required for preparing the coating slurry are calculated based on the preparation of 227g PtO2 for every 319.1g Pt(NO3)2, 172.1g CeO2 for every 434.2g Ce(NO3)3·6H2O, 123.2g ZrO2 for every 429.3g Zr(NO3)4·5H2O and the mass percentage of Al2O3 in aluminum sol; in addition, the mass of polyethylene glycol required for preparing the catalytic coating is calculated based on the ratio of 5 to 15g of polyethylene glycol with an average molecular weight of 20,000 for every 100g of catalytic coating.

[0023] The present invention also provides a diesel engine catalyst prepared by the above preparation method, which is encapsulated as a diesel engine oxidation catalyst, and the oxidation catalyst is installed in the exhaust passage of the diesel engine to achieve efficient oxidation purification of PM, HC and CO in the diesel engine exhaust.

[0024] The beneficial effects of the present invention are:

[0025] The present invention adopts 5-element high entropy metal oxide and a small amount of precious metal Pt to form the main catalytic active component of the diesel engine oxidation catalyst, which can significantly reduce the load of precious metal materials while improving the catalytic performance of the catalyst oxidation reaction, not only reducing the raw material cost of DOC, but also greatly improving the catalyst's resistance to sulfur poisoning, thermal aging, and coking. On the other hand, the present invention adopts a method of first adsorption and then gelation based on carbon black template materials to prepare CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles, which is not only simple to operate, saves preparation time and raw material costs, but also can significantly improve the dispersion effect of CeFeMnCoNiOx five-element high entropy composite metal oxide precursors, which is conducive to the preparation of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles with smaller scale, uniform particle size, and regular structure. The CeFeMnCoNiOx five-element high-entropy composite metal oxide in the form of nanoparticles in the catalytic coating can significantly increase the number of catalytic active sites on the catalyst surface and improve the catalytic activity of the catalytic active sites, thereby optimizing the catalytic performance of the catalyst for pollutant purification reactions, further achieving a reduction in the amount of precious metal materials in DOC and reducing the raw material cost of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0027] Figure 1 Schematic diagram of diesel engine exhaust PM, HC and CO purification performance engine evaluation system.

[0028] Figure 2 In order to utilize the diesel engine exhaust PM, HC and CO purification performance engine evaluation system, the diesel engine exhaust temperature was 300°C and the air velocity was 50000h -1 When the catalysts described in Examples 1 to 3 are used to purify PM, HC and CO in diesel engine exhaust,

[0029] Figure 3 In order to utilize the diesel engine exhaust PM, HC and CO purification performance engine evaluation system, the diesel engine exhaust temperature was 400°C and the air velocity was 100000h -1 When the catalysts described in Examples 1 to 3 are used to purify PM, HC and CO in diesel engine exhaust,

[0030] Figure 4 The diesel engine exhaust PM, HC and CO purification performance engine evaluation system is used to evaluate the purification efficiency of the catalysts described in Examples 1 to 3 on PM, HC and CO in diesel engine exhaust during the European Steady State Cycle (ESC) test.

[0031] Among them: 1-dynamometer; 2-coupling; 3-test diesel engine; 4-intake flowmeter; 5-intake processor; 6-injector; 7-fuel injection control system; 8-exhaust sampling port A; 9-temperature sensor A; 10-diesel oxidation catalyst; 11-temperature sensor B; 12-exhaust sampling port B; 13-selective catalytic reduction catalyst; 14-diesel particulate filter; 15-exhaust sampling mechanism; 16-engine exhaust analyzer; 17-exhaust filter; 18-air pump. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The diesel engine catalyst based on high entropy oxide ultrafine particles includes: CeFeMnCoN i Ox five-element high entropy composite metal oxide nanoparticles, PtO2, CeO2, ZrO2, γ-Al2O3 and 400 mesh cordierite honeycomb ceramics.

[0034] The main catalytic active components are CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2, and the mass percentages of the CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 are: 90-98%: 2-10%, and the sum of the mass percentages is 100%.

[0035] In the CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles, the mol percentages of Ce element, Fe element, Mn element, Co element and Ni element are: 20-35%: 15-25%: 15-25%: 15-25%: 10-20%, and the sum of the mol percentages is 100%.

[0036] CeO2 and ZrO2 are used as promoters, and the mass percentages of CeO2 and ZrO2 are: 70-90%: 10-30%, and the sum of the mass percentages is 100%.

[0037] γ-Al2O3 is used as a coating auxiliary agent, and the γ-Al2O3 comes from pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol, and the mass percentages of the pure γ-Al2O3 powder and the γ-Al2O3 converted from aluminum sol are: 75-90%: 10-25%, and the sum of the mass percentages is 100%.

[0038] The catalytic coating of the catalyst of the present invention is composed of the main catalytic active component, the co-catalyst and the coating additive, and the mass percentages of the main catalytic active component, the co-catalyst and the coating additive are: 2-8%: 3-12%: 80-95%, and the sum of the mass percentages is 100%.

[0039] The catalyst of the present invention is composed of the catalytic coating and 400-mesh cordierite honeycomb ceramics, and the 400-mesh cordierite honeycomb ceramics are the carrier of the catalyst of the present invention, and the catalytic coating needs to be coated on the carrier, and the mass percentage range of the catalytic coating and the carrier is: 15-30%: 85-70%, and the sum of the mass percentages is 100%.

[0040] The preparation method of the catalyst of the present invention is described in detail below through specific examples.

[0041] Example 1

[0042] (1) Catalyst composition design

[0043] The following proportions are designed respectively: the mass percentages of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 are: 90%:10%, the mol percentages of Ce element, Fe element, Mn element, Co element and Ni element in CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles are: 20%:20%:20%:20%:20%, the mass percentages of CeO2 and ZrO2 in the co-catalyst are: 70%:30%, the mass percentages of pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol in the γ-Al2O3 coating additive are: 75%:25%, the mass percentages of the main catalytic active component, the co-catalyst and the coating additive are: 2%:3%:95%, and the planned configuration of the coating slurry can generate 2000g of catalytic coating.

[0044] (2) Preparation of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles

[0045] Weigh 34.7 g Ce(NO3)3·6H2O, 32.3 g Fe(NO3)3·9H2O, 13.8 g Mn(CH3COO)2, 23.3 g Co(NO3)2·6H2O, 23.3 g Ni(NO3)2·6H2O, 144.2 g glucose and 125 g median particle size (D 50The seven raw materials are added into 2.5L deionized water, and ultrasonically oscillated for 2h, and then the mixture of the seven raw materials and deionized water is heated while ultrasonically oscillating, so that the mixture is evaporated to dryness after 8h to form a wet gel; the wet gel is then dried at 80°C for 12h to obtain a dry gel; the dry gel is heated to 350°C at a rate of 3°C:min in a muffle furnace and maintained for 2h, and then heated to 600°C at a rate of 10°C:min and calcined for 6h to obtain CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles.

[0046] (3) Preparation of coating slurry

[0047] Weigh 5.6 g of Pt(NO3)2, 106 g of Ce(NO3)3·6H2O, 62.7 g of Zr(NO3)4·5H2O, 1425 g of pure γ-Al2O3 powder, 2375 g of aluminum sol with an Al2O3 mass content of 20%, 300 g of polyethylene glycol with a molecular weight of 20,000, and the CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles prepared in step (2), add the seven raw materials together into 30 kg of deionized water, and form a slurry by ultrasonic oscillation; adjust the pH value of the slurry to within the range of 4 to 6 with NaOH or HNO3, and grind the slurry on a grinder until D 50 The particle size is in the range of 800 to 1000 nm, and the ground slurry is stirred at 70° C. for 48 hours to obtain a coating slurry.

[0048] (4) Coating

[0049] Weigh 1 kg of the carrier, immerse the carrier in the coating slurry at 70°C, and ensure that the upper end surface of the carrier is slightly higher than the slurry surface; after the slurry is naturally lifted and fills all the pores of the carrier, take the carrier out of the slurry, blow off the residual fluid in the pores, dry at 110°C for 4 hours, and then calcine at 500°C for 4 hours. Repeat the above immersion, drying and calcination process 3 times to obtain a diesel engine catalyst based on ultrafine particles of high entropy oxide.

[0050] Example 2

[0051] (1) Catalyst composition design

[0052] The following proportions are designed respectively: the mass percentages of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 are: 98%:2%, the mol percentages of Ce element, Fe element, Mn element, Co element and Ni element in CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles are: 35%:20%:20%:15%:10%, the mass percentages of CeO2 and ZrO2 in the co-catalyst are: 90%:10%, the mass percentages of pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol in the γ-Al2O3 coating additive are: 90%:10%, the mass percentages of the main catalytic active component, the co-catalyst and the coating additive are: 8%:12%:80%, and the planned configuration of the coating slurry can generate 2000g of catalytic coating.

[0053] (2) Preparation of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles

[0054] Weigh 234g Ce(NO3)3·6H2O, 124.4g Fe(NO3)3·9H2O, 53.3g Mn(CH3COO)2, 67.2g Co(NO3)2·6H2O, 44.8g Ni(NO3)2·6H2O, 280g glucose and 265g median particle size (D 50 The seven raw materials are added into 2.65L deionized water, and ultrasonically oscillated for 4h, and then the mixture of the seven raw materials and deionized water is heated while ultrasonically oscillating, so that the mixture is evaporated to dryness after 6h to form a wet gel; the wet gel is then dried at 110°C for 6h to obtain a dry gel; the dry gel is heated to 350°C at a rate of 3°C:min in a muffle furnace and maintained for 2h, and then heated to 800°C at a rate of 10°C:min and calcined for 3h to obtain CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles.

[0055] (3) Preparation of coating slurry

[0056] Weigh 4.5 g of Pt(NO3)2, 545 g of Ce(NO3)3·6H2O, 83.6 g of Zr(NO3)4·5H2O, 1440 g of pure γ-Al2O3 powder, 800 g of aluminum sol with an Al2O3 mass content of 20%, 100 g of polyethylene glycol with a molecular weight of 20,000, and the CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles prepared in step (2), add the seven raw materials together into 10 kg of deionized water, and form a slurry by ultrasonic oscillation; adjust the pH value of the slurry to within the range of 4 to 6 using NaOH or HNO3, and grind the slurry on a grinder until D 50 The particle size is in the range of 800 to 1000 nm. The ground slurry is stirred at 50° C. for 72 hours to obtain a coating slurry.

[0057] (4) Coating

[0058] Weigh 1 kg of the carrier, immerse the carrier in the coating slurry at 50°C, and ensure that the upper end surface of the carrier is slightly higher than the slurry surface; after the slurry is naturally lifted and fills all the pores of the carrier, take the carrier out of the slurry, blow off the residual fluid in the pores, dry at 80°C for 16 hours, and then calcine at 600°C for 2 hours. Repeat the above immersion, drying and calcination process twice to obtain a diesel engine catalyst based on ultrafine particles of high entropy oxide.

[0059] Example 3

[0060] (1) Catalyst composition design

[0061] The following proportions are designed respectively: the mass percentages of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 are: 95%:5%, the mol percentages of Ce element, Fe element, Mn element, Co element and Ni element in CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles are: 30%:20%:20%:20%:10%, the mass percentages of CeO2 and ZrO2 in the co-catalyst are: 80%:20%, the mass percentages of pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol in the γ-Al2O3 coating additive are: 80%:20%, the mass percentages of the main catalytic active components, co-catalysts and coating additives are: 5%:10%:85%, and the planned configuration of the coating slurry can generate 2000g of catalytic coating.

[0062] (2) Preparation of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles

[0063] Weigh 126.4 g Ce(NO3)3·6H2O, 78.4 g Fe(NO3)3·9H2O, 33.6 g Mn(CH3COO)2, 56.5 g Co(NO3)2·6H2O, 28.2 g Ni(NO3)2·6H2O, 270 g glucose and 260 g median particle size (D 50 The seven raw materials are added into 4L deionized water, ultrasonically oscillated for 3h, and then the mixture of the seven raw materials and deionized water is heated while ultrasonically oscillating, so that the mixture is evaporated to dryness after 7h to form a wet gel; the wet gel is then dried at 100°C for 9h to obtain a dry gel; the dry gel is heated to 350°C at a rate of 3°C:min in a muffle furnace and maintained for 2h, and then heated to 700°C at a rate of 10°C:min and calcined for 4h to obtain CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles.

[0064] (3) Preparation of coating slurry

[0065] Weigh 7 g of Pt(NO3)2, 403.7 g of Ce(NO3)3·6H2O, 139.4 g of Zr(NO3)4·5H2O, 1360 g of pure γ-Al2O3 powder, 1700 g of aluminum sol with an Al2O3 mass content of 20%, 200 g of polyethylene glycol with a molecular weight of 20,000, and the CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles prepared in step (2), add the seven raw materials together into 20 kg of deionized water, and form a slurry by ultrasonic oscillation; adjust the pH value of the slurry to within the range of 4 to 6 using NaOH or HNO3, and grind the slurry on a grinder until D 50 The particle size is in the range of 800 to 1000 nm. The ground slurry is stirred at 60° C. for 60 hours to obtain a coating slurry.

[0066] (4) Coating

[0067] Weigh 1 kg of the carrier, immerse the carrier in the coating slurry at 60°C, and ensure that the upper end surface of the carrier is slightly higher than the slurry surface; after the slurry is naturally lifted and fills all the pores of the carrier, take the carrier out of the slurry, blow off the residual fluid in the pores, dry at 100°C for 8 hours, and then calcine at 550°C for 3 hours. Repeat the above immersion, drying and calcination process 3 times to obtain a diesel engine catalyst based on ultrafine particles of high entropy oxide.

[0068] use Figure 1The diesel engine exhaust PM, HC and CO purification performance engine evaluation system shown in the figure evaluates the diesel engine exhaust PM, HC and CO purification performance of the catalysts prepared in Examples 1 to 3. Before the test, the catalysts prepared in Examples 1 to 3 need to be cut respectively, and the cut catalysts need to be packaged. The test method is:

[0069] (1) Steady-state test: The torque and speed of the test diesel engine 3 are controlled by the dynamometer 1 and the coupling 2, and the fuel supply speed of the injector 6 to the diesel engine is adjusted by the fuel injection control system 7. The ratio of the engine exhaust flow rate to the catalyst volume is controlled to be 50,000 h-1, 50,000 h-2, 50,000 h-3, 50,000 h-4, 50,000 h-5, 50,000 h-6, 50,000 h-7, 50,000 h-8, 50,000 h-9, 50,000 h-10, 50,000 h-11, 50,000 h-12, 50,000 h-13, 50,000 h-14, 50,000 h-15 -1 and 100000h -1 , and successively control the average exhaust temperature in the diesel oxidation catalyst 10 to be 300℃ and 400℃ respectively, and evaluate the PM, HC and CO purification performance. The intake flow measurement value of the intake flow meter 4 provides feedback parameters for the control strategy of the fuel injection control system; and the intake processor 5 provides clean air with a specific temperature and humidity for the engine. The temperature sensor A9 and the temperature sensor B11 respectively measure the exhaust temperature at both ends of the diesel oxidation catalyst 10, and the average exhaust temperature in the diesel oxidation catalyst 10 can be obtained by taking the average of the two temperatures. The exhaust samples before and after the diesel oxidation catalyst 10 are processed enter the exhaust sampling mechanism 15 and the engine exhaust analyzer 16 through the exhaust sampling port A8 and the exhaust sampling port B12 respectively for PM, HC and CO emission analysis, and the exhaust after the exhaust component analysis is discharged out of the laboratory by the air pump 18 after the exhaust gas filter 17 purifies the particulate pollutants. At the same time, the residual exhaust gas of the test diesel engine 3 after sampling is successively purified by the selective catalytic reduction catalyst 13 and the diesel particulate filter 14, and then the particulate pollutants are purified by the exhaust filter 17 and discharged out of the laboratory by the air pump 18. Using the diesel engine exhaust PM, HC and CO purification performance engine evaluation system, the average exhaust temperature in the diesel engine oxidation catalyst is 300°C and the air velocity is 50000h -1 When the average exhaust temperature in the diesel engine oxidation catalyst is 400°C and the air velocity is 100,000h -1 When the catalysts prepared in Examples 1 to 3 have the purification efficiencies for PM, HC and CO in diesel engine exhaust, they are as follows: Figure 2 and Figure 3 shown.

[0070] (2) ESC test: The diesel engine exhaust PM, HC and CO purification performance engine evaluation system was used, and the ESC test procedure specified in the national standard GB 17691-2005 "Emission limits and measurement methods for exhaust pollutants from compression ignition and gas fuel ignition engines for vehicles (China III, IV, V stage)" was used to evaluate the purification effects of the catalysts prepared in Examples 1 to 3 on diesel engine exhaust PM, HC and CO. Figure 4 shown.

[0071] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0072] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A diesel engine catalyst based on ultrafine particles of high entropy oxide, characterized in that: include: CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles, PtO2, CeO2, ZrO2, γ-Al2O3 and 400 mesh cordierite honeycomb ceramics; Among them, CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 are mainly catalytic active components, and the mass percentage of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and PtO2 is 90-98%: 2-10%, and the sum of the mass percentages is 100%.

2. The diesel engine catalyst based on high entropy oxide ultrafine particles according to claim 1, characterized in that: In the CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles, the molar percentages of Ce element, Fe element, Mn element, Co element and Ni element are 20-35%: 15-25%: 15-25%: 15-25%: 10-20%, and the sum of the molar percentages is 100%.

3. The diesel engine catalyst based on high entropy oxide ultrafine particles according to claim 2, characterized in that: CeO2 and ZrO2 are used as promoters, and the mass percentages of CeO2 and ZrO2 are 70-90%: 10-30%, and the sum of the mass percentages is 100%.

4. The diesel engine catalyst based on high entropy oxide ultrafine particles according to claim 3, characterized in that: γ-Al2O3 is used as a coating auxiliary agent, and the γ-Al2O3 comes from pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol, the mass percentages of pure γ-Al2O3 powder and γ-Al2O3 converted from aluminum sol are: 75-90%: 10-25%, and the sum of the mass percentages is 100%.

5. The diesel engine catalyst based on high entropy oxide ultrafine particles according to claim 4, characterized in that: The catalytic coating of the diesel engine catalyst is composed of a main catalytic active component, a co-catalyst and a coating additive, and the mass percentages of the main catalytic active component, the co-catalyst and the coating additive are: 2-8%: 3-12%: 80-95%, and the sum of the mass percentages is 100%.

6. The diesel engine catalyst based on high entropy oxide ultrafine particles according to claim 5, characterized in that: The diesel engine catalyst is composed of the catalytic coating and 400 mesh cordierite honeycomb ceramics, and the 400 mesh cordierite honeycomb ceramics are the carrier of the diesel engine catalyst. The catalytic coating needs to be coated on the carrier, and the mass percentage range of the catalytic coating and the carrier is: 15-30%: 85-70%, and the sum of the mass percentages is 100%.

7. The method for preparing a diesel engine catalyst based on ultrafine high entropy oxide particles according to claim 6, characterized in that: The following steps are involved: Step 1: Catalyst composition design: prepare the following materials in proportion: CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles, PtO2, CeO2, ZrO2, γ-Al2O3; Step 2: Preparation of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles: Weigh the determined masses of Ce(NO3)3·6H2O, Fe(NO3)3·9H2O, Mn(CH3COO)2, Co(NO3)2·6H2O, Ni(NO3)2·6H2O and glucose, and carbon black with a mass ranging from 0.5 to 1 times the sum of the masses of Ce(NO3)3·6H2O, Fe(NO3)3·9H2O, Mn(CH3COO)2, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O and a median particle size not exceeding 500 nm. The seven raw materials are added together into deionized water weighed according to the ratio of 1g carbon black to 10-20mL deionized water, and ultrasonic oscillation is performed for 2-4h, and then the mixture of the seven raw materials and deionized water is heated while ultrasonic oscillation, so that the mixture is evaporated to dryness after 6-8h to form a wet gel; the wet gel is then dried at 80-110°C for 6-12h to obtain a dry gel; the dry gel is heated to 350°C at a rate of 3°C:min in a muffle furnace and maintained for 2h, and then heated to 600-800°C at a rate of 10°C:min and calcined for 3-6h to obtain CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles; Step 3: Preparation of coating slurry: Weigh a certain mass of Pt(NO3)2, Ce(NO3)3·6H2O, Zr(NO3)4·5H2O, pure γ-Al2O3 powder, aluminum sol, polyethylene glycol with a molecular weight of 20,000, and CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles prepared in step 2, add the seven raw materials together into deionized water with a mass equivalent to 5 to 15 times the mass of the planned catalytic coating, and form a slurry by ultrasonic oscillation; adjust the pH value of the slurry to within the range of 4 to 6 with NaOH or HNO3, and grind the slurry on a grinder to D 50 The particle size is in the range of 800 to 1000 nm, and the ground slurry is stirred at 50 to 70° C. for 48 to 72 hours to obtain a coating slurry; Step 4: Coating: Design the mass of the carrier to be coated with the catalytic coating; weigh the determined mass of the carrier, immerse the carrier in the coating slurry at 50-70°C, and ensure that the upper end surface of the carrier is slightly higher than the slurry surface; after the slurry is naturally lifted and fills all the pores of the carrier, take the carrier out of the slurry, blow off the residual fluid in the pores, dry at 80-110°C for 4-16 hours, and then calcine at 500-600°C for 2-4 hours; repeat the above-mentioned impregnation, drying and calcination processes 2-3 times to obtain a diesel engine catalyst based on high entropy oxide ultrafine particles.

8. The method for preparing a diesel engine catalyst based on ultrafine high entropy oxide particles according to claim 1, characterized in that: In step 2, the mass of CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles and the molar numbers of Ce, Fe, Mn, Co and Ni elements in CeFeMnCoNiOx five-element high entropy composite metal oxide nanoparticles are calculated according to step 1; 1 mol Ce is prepared from 434.2g Ce(NO3)3·6H2O, 1 mol Fe is prepared from 404g Fe(NO3)3·9H2O, 1 mol Mn is prepared from 173g Mn(CH3COO)2, 1 mol Co is prepared from 291g Co(NO3)2·6H2O, and 1 mol Ni is prepared from 290.8g Ni(NO3)2·6H2O. Ni, and the ratio of the sum of the molar numbers of Ce, Fe, Mn, Co and Ni elements in CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles to the molar number of glucose is 1:1-2, and the conversion ratio of 180.2g per mol of glucose is used to calculate the masses of Ce(NO3)3·6H2O, Fe(NO3)3·9H2O, Mn(CH3COO)2, Co(NO3)2·6H2O, Ni(NO3)2·6H2O and glucose required to prepare the CeFeMnCoNiOx five-element high-entropy composite metal oxide nanoparticles.

9. The method for preparing a diesel engine catalyst based on ultrafine high entropy oxide particles according to claim 1, characterized in that: In step three, the masses of PtO2, CeO2 and ZrO2 and the mass of γ-Al2O3 coating additive required for preparing the catalytic coating are calculated based on step one; the masses of Pt(NO3)2, Ce(NO3)3·6H2O, Zr(NO3)4·5H2O and aluminum sol required for preparing the coating slurry are calculated based on the preparation of 227g PtO2 for every 319.1g Pt(NO3)2, 172.1g CeO2 for every 434.2g Ce(NO3)3·6H2O, 123.2g ZrO2 for every 429.3g Zr(NO3)4·5H2O and the mass percentage of Al2O3 in aluminum sol; in addition, the mass of polyethylene glycol required for preparing the catalytic coating is calculated based on the ratio of 5 to 15g of polyethylene glycol with an average molecular weight of 20,000 for every 100g of catalytic coating.

10. The diesel engine catalyst prepared according to any one of the preparation methods of claims 7 to 9 is packaged as a diesel engine oxidation catalyst, and the oxidation catalyst is installed in the exhaust passage of the diesel engine to achieve efficient oxidation purification of PM, HC and CO in the diesel engine exhaust.